2015
DOI: 10.1097/jto.0000000000000588
|View full text |Cite
|
Sign up to set email alerts
|

Cabazitaxel Versus Topotecan in Patients with Small-Cell Lung Cancer with Progressive Disease During or After First-Line Platinum-Based Chemotherapy

Abstract: Cabazitaxel, a next-generation taxane, had inferior efficacy when compared with standard-dose topotecan in the treatment of relapsed SCLC. Topotecan remains a suboptimal therapy, and continued efforts to develop improved second-line treatments are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 29 publications
(47 reference statements)
2
28
0
Order By: Relevance
“…Gemcitabine at non-cytotoxic concentrations enables brain tumor radiosensitization [41]. However, it shows only modest potency to penetrate the BBB, resulting in limited therapeutic benefits for intracranial tumors [42]. We first characterized the fluorescence-emitting and cellkilling functions of NIRG.…”
Section: Resultsmentioning
confidence: 99%
“…Gemcitabine at non-cytotoxic concentrations enables brain tumor radiosensitization [41]. However, it shows only modest potency to penetrate the BBB, resulting in limited therapeutic benefits for intracranial tumors [42]. We first characterized the fluorescence-emitting and cellkilling functions of NIRG.…”
Section: Resultsmentioning
confidence: 99%
“…Whether the efficacy signal observed in the present study is sufficient to support a definitive superiority trial in comparison with topotecan in unselected patients is difficult to ascertain, particularly in light of the negative result of the phase II trial of cabazitaxel versus topotecan in a similar population of patients with relapsed SCLC. 7 However, a biomarker-enrichment strategy using c-Myc expression or mutations in cell cycle regulator genes could enhance the likelihood of success of such a comparative study.…”
Section: Discussionmentioning
confidence: 99%
“…5 Because of poor responses to current treatments, there is a critical unmet medical need in patients with SCLC, thereby justifying efforts to evaluate novel targeted agents (with validated predictive biomarkers). 7,8 One potential target is Aurora A kinase (AAK), a key regulator of mitosis. 9 AAK is amplified or overexpressed in several solid tumors, including SCLC, and may play a role in tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…To date, no randomized trial has demonstrated superiority of an experimental arm over topotecan for second-line treatment of SCLC (48,49). However, multiple other chemotherapies have shown activity comparable to topotecan in the second-line setting, including irinotecan (50), paclitaxel (51,52), docetaxel (53), gemcitabine (54,55), vinorelbine (56,57), and temozolomide (58,59).…”
Section: Extensive Stage Sclc: Systemic Therapymentioning
confidence: 99%